Angle and Polarization Insensitive Mid-Infrared Optical Filters Using Dense 2D Array of Nanophotonic Cavity Resonators - Matthew Klein; Shivashankar R. Vangala; Joshua R. Hendrickson; Ivan Avrutsky (IEEE Photonics Journal, 2024)
We report on the design and experimental verification of angle and polarization insensitive mid-infrared filters based on dense arrays of dielectric resonators embedded into a metallic film. We experimentally show filters with 60% peak transmission for angles from 0 to 60 degrees for perpendicular polarization states. We also study the surface plasmonic mode excited due to the periodicity of the micro-resonators in the array. Simulations support the experimental results for both the primary resonance and the plasmonic mode. Integrating these filters with IR detectors offers multispectral imaging and improved search and track capability.